Canopy and Understory Nitrogen Addition Alters Organic Soil Bacterial Communities but Not Fungal Communities in a Temperate Forest - Liu, Yang; Tan, Xiangping; Fu, Shenglei; Shen, Weijun (Frontiers in Microbiology, 2022)
Atmospheric nitrogen (N) deposition is known to alter soil microbial communities, but how canopy and understory N addition affects soil bacterial and fungal communities in different soil layers remains poorly understood. Conducting a six-year canopy and understory N addition experiment in a temperate forest, we showed that soil bacterial and fungal communities in the organic layer exhibited different responses to N addition. The main effect of N addition decreased soil bacterial diversity and altered bacterial community composition in the organic layer, but not changed fungal diversity and community composition in all layers. Soil pH was the main factor that regulated the responses of soil bacterial diversity and community composition to N addition, whereas soil fungal diversity and community composition were mainly controlled by soil moisture and nutrient availability. In addition, compare with canopy N addition, the understory N addition had stronger effects on soil bacterial Shannon diversity and community composition, but had a weaker effect on soil bacteria richness in the organic soil layer. Our study demonstrates that the bacterial communities in the organic soil layer were more sensitive than the fungal communities to canopy and understory N addition, and the conventional method of understory N addition might have skewed the effects of natural atmospheric N deposition on soil bacterial communities. This further emphasizes the importance of considering canopy processes in future N addition studies, and simultaneously evaluating soil bacterial and fungal communities in response to global environmental changes.